Sie sind auf Seite 1von 17

Chapter 7 Miscellaneous Problems

C07S0M.001: If f (x) = cos(1 − e−x ), then f  (x) = −e−x sin(1 − e−x ).


2
C07S0M.002: If f (x) = sin2 (e−x ) = [sin(e−x )] , then f  (x) = −2e−x sin(e−x ) cos(e−x ).

1 − e−x
C07S0M.003: If f (x) = ln(x + e−x ), then f  (x) = .
x + e−x

C07S0M.004: If f (x) = ex cos 2x, then f  (x) = ex cos 2x − 2ex sin 2x.

C07S0M.005: If f (x) = e−2x sin 3x, then f  (x) = 3e−2x cos 3x − 2e−2x sin 3x.
2
C07S0M.006: If g(t) = ln(tet ) = (ln t) + t2 ln e = (ln t) + t2 , then

1 1 + 2t2
g  (t) = + 2t = .
t t
 
 1
C07S0M.007: If g(t) = 3(e − ln t) , then g (t) = 15(e − ln t)
t 5 t 4
e −
t
.
t

C07S0M.008: If g(t) = sin(et ) cos(e−t ), then

g  (t) = et cos(et ) cos(e−t ) + e−t sin(et ) sin(e−t ).

2 + 3x
C07S0M.009: If f (x) = , then
e4x
3e4x − 4(2 + 3x)e4x 3 − 8 − 12x 12x + 5
f  (x) = = =− .
(e4x )2 e4x e4x

1 + et (1 − et )et + (1 + et )et 2et


C07S0M.010: If g(t) = , then g  (t) = = .
1−e t (1 − e )
t 2 (1 − et )2

C07S0M.011: Given xey = y, we apply Dx to both sides and find that

dy dy dy
ey + xey = ; (1 − xey ) = ey ;
dx dx dx
dy ey dy ey
= ; = .
dx 1 − xey dx 1−y

In the last step we used the fact that xey = y to simplify the denominator.

C07S0M.012: Given sin (exy ) = x, we apply Dx to both sides and find that

 
dy dy
[cos (exy ) ] · exy · y + x = 1; xexy [cos (exy ) ] · = 1 − yexy cos (exy ) ;
dx dx
dy 1 − yexy cos (exy )
= .
dx xexy cos (exy )

C07S0M.013: Given ex + ey = exy , we apply Dx to both sides and find that

1
 
dy dy dy
x
e +e y
=exy
y+x ; (ey − xexy ) = yexy − ex ;
dx dx dx
dy yexy − ex
= y .
dx e − xexy

C07S0M.014: Given x = yey , we apply Dx to both sides and obtain

dy dy dy 1 y y
1 = ey + yey ; = y = y = .
dx dx dx e + yey ye + y 2 ey x + xy

We used the fact that yey = x in the simplification in the last step.
Here is an alternative approach to finding dy/dx. Beginning with x = yey , we differentiate with respect
to y and find that

dx dy 1
= ey + yey , so that = y .
dy dx e + yey

C07S0M.015: Given ex−y = xy, we apply Dx to both sides and find that

 
dy dy   dy
e x−y
1− =y+x ; x + ex−y = ex−y − y;
dx dx dx

dy ex−y − y dy xy − y (x − 1)y
= x−y ; = = .
dx e +x dx xy + x (y + 1)x

We used the fact that ex−y = xy to make the simplification in the last step.

C07S0M.016: Given x ln y = x + y, we apply Dx to both sides and find that

x dy dy
ln y +· = 1+ ;
y dx dx
 
x dy
−1 · = 1 − ln y;
y dx
x − y dy
· = 1 − ln y;
y dx
dy y(1 − ln y)
= .
dx x−y

 √
C07S0M.017: Given: y = (x2 − 4) 2x + 1 . Thus

 1/2 1  2  1 1

ln y = ln (x − 4)(2x + 1)
2 1/2
= ln (x − 4)(2x + 1)1/2
= ln(x − 4) + ln(2x + 1) .
2
2 2 2
Therefore

1 dy x 1 5x2 + 2x − 4
· = 2 + = ,
y dx x − 4 2(2x + 1) 2(x2 − 4)(2x + 1)

2
and so
 √
dy 5x + 2x − 4
2 (5x2 + 2x − 4) (x2 − 4) 2x + 1
= y(x) · = .
dx 2(x2 − 4)(2x + 1) 2(x2 − 4)(2x + 1)

C07S0M.018: Given: y = (3 − x2 )1/2 (x4 + 1)−1/4 . Thus

1 1
ln y = ln(3 − x2 ) − ln(x4 + 1),
2 4

and therefore

1 dy x x3 x(3x2 + 1)
· =− − 4 = 2 .
y dx 3−x2 x +1 (x − 3)(x4 + 1)

Thus

dy x(3x2 + 1) x(3x2 + 1)(3 − x2 )1/2 x(3x2 + 1)


= y(x) · 2 =− =− .
dx (x − 3)(x + 1)
4 (3 − x )(x + 1)(x + 1)
2 4 4 1/4 (3 − x2 )1/2 (x4 + 1)5/4


1/3
(x + 1)(x + 2)
C07S0M.019: Given: y = . Then
(x2 + 1)(x2 + 2)

1
ln y = ln(x + 1) + ln(x + 2) − ln(x2 + 1) − ln(x2 + 2) ;
3
 
1 dy 1 1 1 2x 2x
· = + − 2 − 2 ;
y dx 3 x+1 x+2 x +1 x +2

dy 6 − 8x − 9x2 − 8x3 − 9x4 − 2x5


= y(x) · ;
dx 3(x + 1)(x + 2)(x2 + 1)(x2 + 2)

1/3
dy 6 − 8x − 9x2 − 8x3 − 9x4 − 2x5 (x + 1)(x + 2)
= · ;
dx 3(x + 1)(x + 2)(x2 + 1)(x2 + 2) (x2 + 1)(x2 + 2)

dy 6 − 8x − 9x2 − 8x3 − 9x4 − 2x5


= .
dx 3(x + 1)2/3 (x + 2)2/3 (x2 + 1)4/3 (x2 + 2)4/3

C07S0M.020: If y = (x + 1)1/2 (x + 2)1/3 (x + 3)1/4 , then

1 1 1
ln y = ln(x + 1) + ln(x + 2) + ln(x + 3);
2 3 4
1 dy 1 1 1
· = + + ;
y dx 2(x + 1) 3(x + 2) 4(x + 3)

dy 13x2 + 55x + 54 13x2 + 55x + 54


= y(x) · = .
dx 12(x + 1)(x + 2)(x + 3) 12(x + 1)1/2 (x + 2)2/3 (x + 3)3/4

x
C07S0M.021: If y = x(e ) , then

3
1 dy ex
ln y = ex ln x; · = + ex ln x;
y dx x
dy (1 + x ln x)ex dy (1 + x ln x)ex (ex ) 
= y(x) · ; = · x .
dx x dx x

ln x
C07S0M.022: Given: y = (ln x) , x > 1. Then

ln y = (ln x) ln (ln x) ;

1 dy 1 ln x 1 + ln (ln x)
· = ln (ln x) + = ;
y dx x x ln x x
dy 1 + ln (ln x) ln x
= · (ln x) .
dx x

C07S0M.023: By l’Hôpital’s rule,

x−2 1 1
lim = lim = .
x→2 x − 4 x→2 2x
2 4
Without l’Hôpital’s rule,

x−2 x−2 1 1
lim = lim = lim = .
x→2 x2 − 4 x→2 (x + 2)(x − 2) x→2 x + 2 4

sin 2x 2 cos 2x 2·1


C07S0M.024: By l’Hôpital’s rule, lim = lim = = 2.
x→0 x x→0 1 1

1 + cos x − sin x − cos x 1


C07S0M.025: By l’Hôpital’s rule, lim = lim = lim = .
x→π (x − π) 2 x→π 2(x − π) x→π 2 2

C07S0M.026: By l’Hôpital’s rule (applied three times),

x − sin x 1 − cos x sin x cos x 1


lim = lim = lim = lim = .
x→0 x3 x→0 3x2 x→0 6x x→0 6 6

C07S0M.027: By l’Hôpital’s rule (applied three times),

tan t − sin t sec2 t − cos t


lim 3
= lim
t→0 t t→0 3t2
2 sec2 t tan t + sin t 4 sec2 t tan2 t + 2 sec4 t + cos t 1
= lim = lim = .
t→0 6t t→0 6 2

ln(ln x) 1
C07S0M.028: By l’Hôpital’s rule, lim = lim = 0.
x→∞ ln x x→∞ ln x

C07S0M.029: By l’Hôpital’s rule,

ln(1 + x) 1 1
lim (cot x) ln(1 + x) = lim = lim = = 1.
x→0 x→0 tan x x→0 (1 + x) sec2 x 1·1

4
C07S0M.030: By l’Hôpital’s rule and the product rule for limits,
 2  
e1/x − 1 e1/x sin x 1/x
lim (e1/x − 1) tan x = lim = lim+ 2 = lim e = 1 · lim e1/x
= +∞.
x→0 + + x→0 cot x x→0 x csc2 x x→0+ x x→0+

Recall that l’Hôpital’s rule is valid even if the resulting limit is +∞ or −∞, although we are stretching the
hypotheses of the product rule a little here. We need a lemma.
Lemma: If

lim f (x) = p > 0 and lim g(x) = +∞,


x→a+ x→a+

then lim f (x) · g(x) = +∞.


x→a+

Proof: Given M > 0, choose δ > 0 such that, if x − a < δ then f (x) > p/2 and g(x) > 2M/p. Then,
for such x, f (x) · g(x) > (p/2) · 2M/p = M . Because M may be arbitrarily large positive, this implies that
f (x) · g(x) takes on arbitrarily large values if x > a and x is near a. That is,

lim f (x) · g(x) = +∞.


x→a+

C07S0M.031: After combining the two fractions, we apply l’Hôpital’s rule once, then use a little algebra:

  sin x
1 1 1 − cos x − x2 (sin x) − 2x −2
lim − = lim 2 = lim = lim x .
x→0 x2 1 − cos x x→0 x (1 − cos x) x→0 2x(1 − cos x) + x2 sin x x→0 2(1 − cos x) + x sin x

Now if x is close to (but not equal to) zero, (sin x)/x ≈ 1, so the numerator in the last limit is near −1.
Moreover, for such x, cos x < 1 and x and sin x have the same sign, so the denominator in the last limit is
close to zero and positive. Therefore the limit is −∞.

C07S0M.032: We don’t need l’Hôpital’s rule here, although it may be applied. Without it we obtain

  3
x2 x3 3x2 − 2x3 −2 0−2
lim − 2 = lim 3 = lim x = = −2.
x→∞ x+2 x +3 x→∞ x + 2x2 + 3x + 6 x→∞ 2 3 6 1+0+0+0
1+ + 2 + 3
x x x
Using l’Hôpital’s rule (three times) we find that
 
x2 x3 3x2 − 2x3
lim − 2 = lim
x→∞ x+2 x +3 x→∞ x3 + 2x2 + 3x + 6
6x − 6x2 6 − 12x −12
= lim = lim = lim = −2.
x→∞ 3x2 + 4x + 3 x→∞ 6x + 4 x→∞ 6

C07S0M.033: Here it is easier not to use l’Hôpital’s rule:

 √  x2 − x − 1 − x
lim x2 − x − 1 − x = lim √ √
x→∞ x→∞ x2 − x − 1 + x
1
x2 − 2x − 1 x−2−
= lim √ √ = lim  x  = +∞.
x→∞ x2 − x − 1 + x x→∞ 1 1 1
1− − 2 −
x x x

5
  ln x 1
C07S0M.034: ln lim x1/x = lim ln x1/x = lim = lim = 0. Therefore lim x1/x = 1.
x→∞ x→∞ x→∞ x x→∞ x x→∞

C07S0M.035: First we need an auxiliary result:

2x 2
lim 2xe−2x = lim = lim = 0.
x→∞ x→∞ e2x x→∞ 2e2x

Then

 ln(e2x − 2x)
ln lim (e2x − 2x)1/x = lim ln(e2x − 2x)1/x = lim
x→∞ x→∞ x→∞ x
2e2x − 2 2 − 2e−2x 2−0
= lim = lim −2x
= = 2.
x→∞ e − 2x
2x x→∞ 1 − 2xe 1−0
Therefore lim (e2x − 2x)1/x = e2 .
x→∞

1/x2
C07S0M.036: Given: lim 1 − exp(−x2 ) .
x→∞

 
1/x2  2
2 1/x ln 1 − exp(−x2 )
ln lim 1 − exp(−x )2
= lim ln 1 − exp(−x ) = lim
x→∞ x→∞ x→∞ x2
2x exp(−x2 ) exp(−x2 ) 0
= lim = lim = = 0.
x→∞ 2x [1 − exp(−x2 )] x→∞ 1 − exp(−x2 ) 1−0
1/x2
Therefore lim 1 − exp(−x2 ) = e0 = 1.
x→∞

C07S0M.037: This is one of the most challenging problems in the book. We deeply regret publication of
this solution. First let u = 1/x. Then
 x

1 (1 + u)1/u − e
L = lim x · 1+ − e = lim .
x→∞ x u→0+ u

Apply l’Hôpital’s rule once:


 
1/u u − (1 + u) ln(1 + u)
L = lim (1 + u) .
u→0+ u2 (1 + u)

Now apply the product rule for limits!


 
u − (1 + u) ln(1 + u)
L=e· lim .
u→0+ u2 (1 + u)

Finally apply l’Hôpital’s rule twice:


   
1 − 1 − ln(1 + u) −1 −1 e
L=e· lim =e· lim =e· =− .
u→0+ 2u + 3u2 u→0+ (1 + u)(2 + 6u) 1·2 2

Most computer algebra programs cannot evaluate the original limit.

C07S0M.038: First replace b with x to remind us what the variable in this problem is. Thus
  √ 
x a x + x2 − a2
A(x) = 2πax +√ ln .
a x2 − a2 a

6
Then
 

2πa2 x x + (x2 − a2 )1/2


lim A(x) = lim 2πx2 + ln
x→a x→a+ (x − a2 )1/2
2 a
 

x x + (x2 − a2 )1/2
= 2πa2 + 2πa2 lim ln .
x→a+ (x2 − a2 )1/2 a
Then apply l’Hôpital’s rule to the limit that remains:

x ln(x + (x2 − a2 )1/2 ) − x ln a


lim
x→a (x2 − a2 )1/2
 
  x 1 2 2 −1/2
ln x + (x2 − a2 )1/2 + · 1 + (x − a ) · 2x − ln a
x + (x2 − a2 )1/2 2
= lim
x→a 1 2
(x − a2 )−1/2 · 2x
2
  x 
(x2 − a2 )1/2 ln x + (x2 − a2 )1/2 + · (x 2
− a 2 1/2
) + x − (x2 − a2 )1/2 ln a
x + (x2 − a2 )1/2
= lim
x→a+ x
 
(x − a ) ln x + (x − a )
2 2 1/2 2 2 1/2
+ x − (x − a2 )1/2 ln a
2
= lim = 1.
x→a+ x

Therefore A(b) → 4πa2 as b → a+ .

C07S0M.030: Let u = 1 − 2x. Then dx = − 12 du, and so


 
dx 1 1 1 1
=− du = − ln |u| + C = − ln |1 − 2x| + C.
1 − 2x 2 u 2 2

C07S0M.040: Let u = 1 + x3/2 . Then du = 32 x1/2 dx, so that x1/2 dx = 2


3 du. Hence
 
x1/2 2 1 2 2 
dx = du = ln u + C = ln 1 + x3/2 + C.
1 + x3/2 3 u 3 3

C07S0M.041: Let u = 1 + 6x − x2 . Then du = (6 − 2x) dx, so that (3 − x) dx = 12 du. Thus


 
3−x 1 1 1 1
dx = du = ln |u| + C = ln |1 + 6x − x2 | + C.
1 + 6x − x2 2 u 2 2

C07S0M.042: Let u = ex + e−x . Then du = (ex − e−x ) dx, so that


 
ex − e−x 1  
dx = du = (ln u) + C = ln ex + e−x + C.
ex + e−x u

C07S0M.043: Let u = 2 + cos x. Then du = − sin x dx, and thus


 
sin x 1
dx = − du = −(ln u) + C = − ln(2 + cos x) + C.
2 + cos x u


e−1/x
2
1
dx = e−1/x + C. (Optional substitution: u = −1/x2 .)
2
C07S0M.044:
x3 2

7

x
C07S0M.045: Let u = 10 . Then

√ 1 10 x ln 10
du = (10 x
ln 10) · x−1/2 dx = √ · dx.
2 x 2

Therefore
 √  √
10 x
2 2u 2 · 10 x
√ dx = du = +C = + C.
x ln 10 ln 10 ln 10

1
C07S0M.046: Let u = ln x. Then du = dx, so that
x
 
1 1 1 1
dx = du = − + C = − + C.
x(ln x)2 u2 u ln x

C07S0M.047: Let u = 1 + ex . Then du = ex dx, and thus


 
2 2
ex (1 + ex )1/2 dx = u1/2 du = u3/2 + C = (1 + ex )3/2 + C.
3 3

1
C07S0M.048: Let u = 1 + ln x. Then du = dx, and therefore
x
 
1 2 2
(1 + ln x)1/2 dx = u1/2 du = u3/2 + C = (1 + ln x)3/2 + C.
x 3 3

 
6x
C07S0M.049: 2x · 3x dx = 6x dx = + C.
ln 6

2 −1/3
C07S0M.050: Let u = 1 + x2/3 . Then du = x dx. Hence
3
 
dx 3 1 3 3
= du = (ln u) + C = ln(1 + x2/3 ) + C.
x1/3 (1 + x2/3 ) 2 u 2 2

C07S0M.051: The revenue realized upon selling after t months will be


 
t 12 − 24 ln 2 − t ln 2
f (t) = B · 2 + · 2−t/12 , for which f  (t) = B · .
12 144 · 2t/12

Thus f  (t) = 0 when

12 − 24 ln 2
t= ≈ −6.68765951.
ln 2
But this value of t is negative, and in addition f  (t) < 0 for all larger values of t. Thus the revenue is a
decreasing function of t for all t  0. Therefore the grain should be sold immediately.

C07S0M.052: The profit will be


√  1 
2 t − 1000 exp 10 t .
1
f (t) = 800 exp

Now

8
 √   1 
 100 2 exp 12 t − t1/2 exp 10 t
f (t) = 1/2
,
t

We used Newton’s method to solve f  (t) = 0 and found the solution to be approximately 11.7519277504.
To make sure that this value of t maximizes the profit, we graphed f (t) for 0  t  21 (the graph is shown
following this solution). The profit upon cutting and selling after about 11.75 years will be approximately
$1202.37.
1200

1000

800

600

400

200

5 10 15 20
-200

C07S0M.053: If lots composed of x pooled samples are tested, there will be 1000/x lots, so there will be
1000/x tests. In addition, if a lot tests positive, there will be x additional tests. The probability of a lot
testing positive is 1 − (0.99)x , so the expected number of lots that require additional tests will be the product
of the number of lots and the probability 1 − (0.99)x that a lot tests positive. Hence the total number of
tests to be expected will be

1000 1000 1000


f (x) = + [1 − (0.99)x ] · x = + 1000 − 1000(0.99)x
x x x

if x  2. Next,

1000
f  (x) = − − 1000(0.99)x ln(0.99);
x2
1
f  (x) = 0 when = (0.99)x ln(100/99);
x2

(0.99)−x
x2 = ;
ln(100/99)

(0.99)−x/2
x=  .
ln(100/99)

The form of the last equation is exactly what we need to implement the method of repeated substitution
(see Problems 23 through 25 of Section 3.8). We substitute our first “guess” x0 = 10 into the right-hand side
of the last equation, thus obtaining a “better” (we hope) value x1 and continue this process until the digits
in these successive approximations stabilize. Results: x1 = 10.488992, x2 = 10.514798, x3 = 10.516161,
x4 = 10.516233, and x5 = 10.516237 = x6 . The method is not as fast as Newton’s method but the formula
is simpler. (The graph of y = f (x) follows this solution to convince you that we have actually found the
minimum value of f .) We must use an integral number of samples, so we find that f (10) ≈ 195.618 and
f (11) = 195.571, so there should be 90 lots of 11 samples each and one lot of 10 for the most economical
results. Alternatively, it might be simpler to use 10 samples in every lot; the extra cost would be only about

9
24 cents. The total cost of the batch method will be about $978, significantly less than the $5000 cost of
testing each sample individually.

500

450

400

350

300

250

10 20 30 40

C07S0M.054: If f (x) = 12 x2 − 1
4 ln x, then
 2  2
 2 1 1 1 1
1 + [f (x) ] = 1 + x − 2
=x + + = x+ .
4x 2 16x2 4x

Therefore the arc length is


  
e
e
1 1 2 1 1 1 2 1 2e2 − 1
x+ dx = x + ln x = + e − = ≈ 3.4445280495.
1 4x 2 4 1 4 2 2 4

1 3
C07S0M.055: If f (x) = sin−1 3x, then f  (x) =  · Dx (3x) = √ .
1− (3x)2 1 − 9x2

7
C07S0M.056: If f (x) = tan−1 7x, then f  (x) = .
1 + 49x2

C07S0M.057: If g(t) = sec−1 t2 , then

1   2t 2
g  (t) =  · Dt t2 = √ = √ .
|t2 | (t2 )2 −1 t2 t −1
4 t t −1
4

et
C07S0M.058: If g(t) = tan−1 et , then g  (t) = .
1 + e2t

C07S0M.059: If f (x) = sin−1 (cos x), then

1 sin x sin x
f  (x) =  · Dx (cos x) = − √ =− .
2 1 − cos2 x | sin x|
1 − (cos x)

2
C07S0M.060: If f (x) = sinh−1 2x, then f  (x) = √ .
1 + 4x2

1 10
C07S0M.061: If g(t) = cosh−1 10t, then g  (t) =  · Dt (10t) = √ , t> 1
10 .
(10t)2 − 1 100t2 − 1
 
1
C07S0M.062: If h(u) = tanh−1 , then
u

10
 
1 1 u2 1 1 1
h (u) =  2 · Du =− 2 · 2 =− 2 =
1 u u −1 u u −1 1 − u2
1−
u

provided that |u| > 1.


 
−1 1
C07S0M.063: If f (x) = sin , then
x2
 
 1 1 1 −2 2
f (x) =   2 · Dx = · =− √ .
1 x2 1 x3 x x −1
4
1− 1−
x2 x4

 
−1 1
C07S0M.064: If f (x) = tan , then
x
 
 1 1 x2 −1 1
f (x) = · Dx = 2 · =− 2
1 x x + 1 x2 x +1
1+ 2
x
provided that x = 0.

C07S0M.065: If f (x) = arcsin x, then

1  1 1 1
f  (x) =  · Dx x1/2 = √ · x−1/2 = √ √ .
√ 2 1 − x 2 2 1 − x x
1 − ( x)

C07S0M.066: If f (x) = x sec−1 x2 , then

x   2
f  (x) =  · Dx x2 + sec−1 x2 = √ + sec−1 x2
|x2 | (x2 )2 −1 x −1
4

C07S0M.067: If f (x) = tan−1 (x2 + 1), then

1 2x
f  (x) = · Dx (x2 + 1) = 4 .
1 + (x2 + 1)2 x + 2x2 + 2


C07S0M.068: If f (x) = sin−1 1 − x2 , then

1 1 1 x
f  (x) =  · Dx (1 − x2 )1/2 = √ · (1 − x2 )−1/2 · (−2x) = − √ .
1 − (1 − x2 ) x2 2 |x| 1 − x2

C07S0M.069: If f (x) = ex sinh ex , then f  (x) = e2x cosh ex + ex sinh ex .

sinh x
C07S0M.070: If f (x) = ln cosh x, then f  (x) = = tanh x.
cosh x

C07S0M.071: If f (x) = tanh2 3x + sech2 3x, then f (x) ≡ 1 by Eq. (5) in Section 7.6. Therefore f  (x) ≡ 0.
Alternatively, f  (x) = 6 tanh 3x sech2 3x − 6 sech 3x sech 3x tanh 3x ≡ 0.

11

C07S0M.072: If f (x) = sinh−1 x2 − 1, then

1 1 1 x
f  (x) =  √ 2 · Dx (x − 1)
2 1/2
=√ · (x2 − 1)−1/2 · 2x = √ .
1+ x2 − 1 1+x −1
2 2 |x| x2 − 1


C07S0M.073: If f (x) = cosh−1 x2 + 1, then

1 1 1 2 x
f  (x) = √ 2 · Dx (x2 + 1)1/2 = √ · (x + 1)−1/2 · 2x = √ .
x2 + 1 −1 x2 2 |x| x2 + 1

C07S0M.074: If f (x) = tanh−1 (1 − x2 ), then

1 −2x 2
f  (x) = · (−2x) = 2 = 3 .
1 − (1 − x2 )2 2x − x4 x − 2x

C07S0M.075: Let u = 2x. Then du = 2 dx, so


 
1 1 1 1 1
√ dx = √ du = sin−1 u + C = sin−1 2x + C.
1 − 4x2 2 1 − u2 2 2

C07S0M.076: Let u = 2x. Then du = 2 dx, so


 
1 1 1 1 1
dx = du = arctan u + C = arctan 2x + C.
1 + 4x2 2 1 + u2 2 2

√ √ √
C07S0M.077: Let x = 2u. Then dx = 2 du and 4 − x2 = 4 − 4u2 = 2 1 − u2 . Therefore
  x
1 2
√ dx = √ du = arcsin u + C = arcsin + C.
4 − x2 2 1 − u2 2

C07S0M.078: Let x = 2u. Then dx = 2 du and 4 + x2 = 4(1 + u2 ). Thus


   x
1 2 1 1 1 1
dx = du = du = arctan u + C = arctan + C.
4 + x2 2
4(1 + u ) 2 1 + u2 2 2 2

√ √
C07S0M.079: Let u = ex . Then du = ex dx and 1 − e2x = 1 − u2 . Hence
 
ex 1
√ dx = √ du = arcsin u + C = arcsin ex + C.
1 − e2x 1 − u2

C07S0M.080: Let u = x2 . Then du = 2x dx and 1 + x4 = 1 + u2 . Therefore


 
x 1 1 1 1
4
dx = 2
du = arctan u + C = arctan x2 + C.
1+x 2 1+u 2 2

Mathematica 3.0 returns the answer


 
1 1
− arctan + C,
2 x2

12
demonstrating that your intelligence, guided by experience, is still required to interpret what the computer
tells you.
√ √ √
C07S0M.081: Let u = 23 x, so that x = 32 u. Then dx = 3
2 du and 9 − 4x2 = 9 − 9u2 = 3 1 − u2 . So
   
1 3 1 1 1 1 2x
√ dx = · √ du = arcsin u + C = arcsin + C.
9 − 4x2 2 3 1 − u2 2 2 3

C07S0M.082: Let u = 23 x, so that x = 32 u. Then dx = 3


2 du and 9 + 4x2 = 9 + 9u2 = 9(1 + u2 ). Thus
   
1 3 1 1 1 1 2x
dx = · du = arctan u + C = arctan + C.
9 + 4x2 2 9 1 + u2 6 6 3

C07S0M.083: The integrand resembles the derivative of the inverse tangent of something, so we let u = x3 .
Then du = 3x2 dx, so that x2 dx = 13 du. Then
 
x2 1 1 1 1
6
dx = 2
du = arctan u + C = arctan x3 + C.
1+x 3 1+u 3 3

C07S0M.084: If necessary, use the substitution u = sin x, but by inspection,



cos x
dx = arctan(sin x) + C.
1 + sin2 x
Note that while expressions such as sin(arctan x) can be simplified to algebraic functions, expressions such
as arctan(sin x) normally cannot be further simplified.
√ √
C07S0M.085: Let u = 2x. Then du = 2 dx and 4x2 − 1 = u2 − 1. Thus
  
1 1 1 1
√ dx = √ du = √ du = arcsec |u| + C = arcsec |2x| + C.
x 4x2 − 1 2 1
2 u u 2−1 u u2 − 1

Mathematica 3.0 returns the equivalent alternative answer


  
1 1
√ dx = − arctan √ + C,
x 4x2 − 1 4x2 − 1
 
which in turn is equal to arctan 4x2 − 1 + C.

C07S0M.086: The integrand resembles


√ the derivative
√ of the inverse secant function, so we try the substi-
tution u = x . Then du = 2x dx and x − 1 = u − 1, and thus
2 4 2

  
1 1 2x 1 1 1 1
√ dx = √ dx = √ du = arcsec |u| + C = arcsec x2 + C.
x x −1
4 2 x x −1
2 4 2 u u2 −1 2 2

Mathematica 3.0 returns the equivalent answer


  
1 1 1
√ dx = − arctan √ + C,
x x4 − 1 2 x4 − 1
1  
which itself is equal to arctan x4 − 1 + C.
2
13
C07S0M.087: The integrand is slightly√ evocative
√ of the derivative of the inverse secant function, so we
try the substitution u = ex , so that e2x − 1 = u2 − 1 . Then du = ex dx, so
  
1 ex 1
√ dx = √ √
du = arcsec |u| + C = arcsec (ex ) + C.
dx =
e2x −1 ex e2x − 1
−1 u u2
 
Mathematica 3.0 returns the equivalent answer arctan e2x − 1 + C.

C07S0M.088: Use the substitution u = x3 if necessary, but by inspection



1
x2 cosh x3 dx = sinh x3 + C.
3


C07S0M.089: Let u = x if necessary, but by inspection an antiderivative is f (x) = k cosh x1/2 for some
constant k. Because
  k sinh x1/2
f  (x) = k sinh x1/2 · Dx x1/2 = ,
2x1/2
it follows that k = 2 and therefore that
 √
sinh x √
√ dx = 2 cosh x + C.
x

C07S0M.090: Let u = 3x − 2 if necessary, but by inspection an antiderivative is f (x) = k tanh(3x − 2) for


some constant k. Because f  (x) = 3k sech2 (3x − 2), it follows that k = 13 , and thus that

1
sech2 (3x − 2) dx = tanh(3x − 2) + C.
3

Mathematica 3.0 returns the equivalent answer



1
sech2 (3x − 2) dx = − tanh(2 − 3x) + C.
3
Figure 7.6.3 shows why the two answers are really the same.

C07S0M.091: Let u = arctan x if necessary, but evidently



arctan x 1
dx = (arctan x)2 + C.
1 + x2 2

√ √
C07S0M.092: Let u = 2x, so that 4x2 − 1 = u2 − 1 and du = 2 dx. Then
 
1 1 1 1 1
√ dx = √ du = cosh−1 u + C = cosh−1 2x + C.
4x2 − 1 2 u2 − 1 2 2

√ √ √
C07S0M.093: Let u = 23 x, so that x = 32 u. Then dx = 32 du and 4x2 + 9 = 9u2 + 9 = 3 u2 + 1.
Therefore
   
1 3 1 1 1 1 2x
√ dx = · √ du = sinh−1 u + C = sinh−1 + C.
4x2 + 9 2 3 u2 + 1 2 2 3

14

C07S0M.094: We expect to see an integrand containing u2 + 1, so let u = x2 . Then du = 2x dx, and
thus
 
x 1 1 1 1
√ dx = √ du = sinh−1 u + C = sinh−1 x2 + C.
x4 + 1 2 u2 + 1 2 2

C07S0M.095: The volume is


 √
1/ 2
2πx
V = √ dx.
0 1 − x4

Let u = x2 . Then du = 2x dx, and hence


 
2πx 1
√ dx = π √ du = π arcsin u + C = π arcsin x2 + C.
1−x 4 1 − u2
Therefore

1/√2
π2
V = π arcsin x2 = = ζ(2) ≈ 1.644934066848226436472415.
0 6

See the Index in the textbook for references to further information on the Riemann zeta function ζ(z).

C07S0M.096: The volume is


 1
2πx
V = √ dx.
0 x4 + 1

Let u = x2 . Then du = 2x dx, and therefore


 
2πx π
√ dx = √ du = π sinh−1 u + C = π sinh−1 x2 + C.
4
x +1 2
u +1

1 √ 
Thus V = π sinh−1 x2 = π sinh−1 1 = π ln 1 + 2 ≈ 2.7689167860.
0

C07S0M.097: We use some results in Section 7.6. By Eqs. (36) and (37),

  1
−1 1 1 1+ x 1 x+1
tanh = ln = ln = coth−1 x
x 2 1 2 x−1
1−
x
(provided that |x| > 1). By Eq. (35), if 0 < x  1 then

      √   √ 
−1 1 1 1 1 1 − x2 1 + 1 − x2
cosh = ln + − 1 = ln + √ = ln = sech−1 x
x x x2 x x2 x

by Eq. (38). Note that x2 = x because x > 0.

C07S0M.098: If k = 0 and x(t) = A cosh kt + B sinh kt, then

x (t) = kA sinh kt + kB cosh kt and x (t) = k 2 A cosh kt + k 2 B sinh kt = k 2 x(t).

15
If x(0) = 1 and x (0) = 0, then A = 1 and kB = 0, so A = 1 and B = 0. If x(0) = 0 and x (0) = 1, then
A = 0 and kB = 1, so A = 0 and B = 1/k.

C07S0M.099: The graphs of y = cos x and y = sech x are shown following this solution, graphed for
0  x  6. One wonders if there is a solution of cos x = sech x in the interval (0, π/2). We graphed
y = f (x) = sech x − cos x for 0  x  1 and it was clear that f (x) > 0 if x > 0.25. We graphed y = f (x)
for 0  x  0.25 and it was clear that f (x) > 0 if x > 0.06. We repeated this process several times and
could see that f (x) > 0 if x > 0.0002. Instability in the hardware or software made further progress along
these lines impossible. Methods of Section 11.8 can be used to show the desired inequality, but Ted Shifrin
provided the following elegant argument.
First, sech x  1  sec x if x is in I = [0, π/2). Moreover, sech x = sec x only for x = 0 in that interval;
otherwise, sech x < sec x for x in J = (0, π/2). So sech2 x < sec2 x if x is in J.
But tanh x = tan x if x = 0. Therefore tanh x < tan x for x in J because Dx tanh x < Dx tan x for
such x. That is,

sinh x sin x
<
cosh x cos x
if x is in J. All the expressions involved here are positive, so

sinh x cos x < cosh x sin x

if x is in J. That is,

− cosh x sin x + sinh x cos x < 0

for x in J. But cosh x cos x = 1 if x = 0, and we have now shown that Dx (cosh x cos x) < 0 if x is in J.
Therefore

cosh x cos x < 1

for x in J. In other words, sech x  cos x for x in I and sech x > cos x for x in J.
Because cos x  0 < sech x for π/2 < x < 3π/2 and because cos x is increasing, while sech x is
decreasing, for 3π/2  x < 2π, it follows that the least positive solution of f (x) = 0 is slightly larger than
3π/2, about 4.7, exactly as the figure suggests.
We then applied Newton’s method to the solution of f (x) = 0 with x0 = 4.7, with the following results:
x1 ≈ 4.7300338216, x2 ≈ 4.7300407449, x3 ≈ 4.7300407449. Thus x3 is a good approximation to the least
positive solution of cos x cosh x = 1.

0.5

1 2 3 4 5 6

-0.5

-1

16
C07S0M.100: If f (x) = sinh−1 (tan x), then

sec2 x sec2 x sec2 x


f  (x) = √ =√ = = | sec x|.
1 + tan x 2
sec2 x | sec x|

Therefore

sec x dx = sinh−1 (tan x) + C

if sec x > 0; that is, if k is an odd integer and kπ/2 < x < (k + 2)π/2. On the intervals where sec x < 0, we
find that

sec x dx = − sinh−1 (tan x) + C.

Next, if g(x) = tan−1 (sinh x), then

cosh x cosh x
g  (x) = 2 = = sech x,
1 + sinh x cosh2 x
and therefore

sech x dx = tan−1 (sinh x) + C

for all x.

C07S0M.101: Given f (x) = x1/2 , let F (x) = f (x) − ln x. Then

1 1 x1/2 − 2
F  (x) = 1/2
− = ,
2x x 2x
so F  (x) = 0 when x = 4. Clearly F is decreasing on (0, 4) and increasing on (0, +∞), so the global
minimum value of F (x) is

F (4) = 2 − ln 4 = 2 − 2 ln 2 > 2 − 2 · 1

because ln 2 < 1. Therefore f (x) > ln x for all x > 0.


For part (b), we need to solve x1/3 − ln x = 0. The iteration of Newton’s method takes the form

x1/3 − ln x
x ←− x − .
1 −2/3 1
x −
3 x
Beginning with x0 = 100, we get x5 ≈ 93.354461.
For part (c), suppose that j(x) = x1/p is tangent to the graph of g(x) = ln x at the point (q, ln q). Then
q 1/p
= ln q and j  (q) = g  (q). Hence

1 (1/p)−1 1
q = ; q 1/p = p;
p q
p = ln q = ln pp = p ln p; ln p = 1, so p = e.

17